OHIP-14 Scores in Patients with Sjögren's Syndrome Compared to Sicca Syndrome: A Systematic Review with Meta-Analysis - Rossana Izzetti; Elisabetta Carli; Stefano Gennai; Filippo Graziani; Marco Nisi (Hindawi Limited, 2024)
Objectives. Primary Sjögren's syndrome (pSS) is a chronic autoimmune disorder characterized by dryness of mucous membranes, predominantly the eyes and mouth, following glandular tissue substitution. The onset of oral dryness constitutes a significant source of discomfort that negatively affects overall quality of life. This systematic review aimed at investigating the differences in Oral Health Impact Profile-14 (OHIP-14) questionnaire scores in patients diagnosed with Sjögren's syndrome compared to sicca syndrome, to assess the influence of the two conditions on oral health. Study Design. A systematic electronic and manual search was performed up to December 2023 for studies reporting OHIP-14 questionnaire scores in pSS patients versus sicca syndrome. Two authors independently reviewed, selected, and extracted the data. The outcome was the assessment of OHIP-14 scores in studies comparing pSS- and sicca syndrome-affected patients. Meta-analysis was conducted on available quantitative data. Results. Literature search retrieved 30 articles, and 3 articles met the criteria for inclusion in the review. Meta-analysis revealed significantly higher scores in patients with sicca syndrome compared to pSS, although salivary flow was markedly reduced in pSS. Conclusions. While offering supplementary information to standard tests and supporting the assessment of pSS and sicca syndrome patients, further validation is necessary to establish OHIP-14 validity in determining the impact of pSS and sicca syndrome on patients' quality of life.